OP49 Wellbeing of family carers of people who died of cancer: preliminary results of the action advanced care planning (ACP) trial. Issue Volume 9: Issue (2019)Supplement 2 (3rd December 2019) - Vandenbogaerde, I; de Vleminck, A; Cohen, J; Verkissen, MN; Lapeire, L; Ingravallo, F; Payne, S; Wilcock, A; Seymour, J; Kars, MC; Lunder, U; Christensen, CA; et al.
Abstract : Background: Previous studies showed that family carers (FCs) who engaged in formal ACP had fewer adverse outcomes in wellbeing compared with FCs who did not. The ACTION trial is the first multicentre randomized controlled trial of ACP in six European countries. This study will report on the effect of ACP on the wellbeing of bereaved FCs. Methods: 451 questionnaires were sent to bereaved FCs 3 months after the patient participating in the trial had died; 163 were returned (response rate: 36.1%; N control= 93, N intervention= 70). Wellbeing was measured with the Hospital Anxiety and Depression Scale (HADS) and Impact Event Scale (IES). Results: No significant differences were found in wellbeing of FCs between groups. The mean scores for the HADS show no significant differences between groups for a nxiety (mean score control 7, 09 vs. mean score intervention 8, 29) and depression (mean score control 6, 72 vs. mean score intervention 7, 17). No significant differences are found between groups in the mean scores for the IES. Intrusion had a mean score of 21, 27 for control vs. 21, 38 for intervention; Avoidance had a mean score of 10, 34 for control vs. 12, 72 for intervention. Conclusion: Despite previous evidence about improved outcomes for wellbeing in FCs in ACP programs, our ACP intervention did not show differences between groups. Possibly the non-response or cultural discrepancies between the different countries have a part in this. More research is needed to explain what mechanisms are present. This study is supported by a grant from the FWO (nr. G034717N).